Potential of Small‐Angle Neutron Scattering for Evaluating Protein Locus within a Polymersome. Issue 1 (10th January 2023) - Palinske, Max; Muza, Upenyu L.; Moreno, Silvia; Appelhans, Dietmar; Boye, Susanne; Schweins, Ralf; Lederer, Albena
Abstract : Inside Cover : In article 2200300 by Albena Lederer and co‐workers, a specific amphiphilic copolymer structure defines the formation of polymersomes, which mimic diffusion processes through biological membranes. The locus of the cargo and the membrane conformation after diffusion are still open questions. Small‐angle neutron scattering in combination with multidetecton fractionation opens new opportunities to evaluate membrane alteration after post‐loading.